Audit committee evaluation in South Africa’s public sector : the 360-degree approach - Motubatse, K. N. (International Conference on Public Administration and Development Alternatives, 2018)
Although the desire and need to assess audit committees’ effectiveness is a growing phenomenon, there is no single way of evaluating their performance, or to determine if the execution of their mandates is more/less effective in the public/private sector. The problem is that audit committees have traditionally been assessed according to a single set of measurements based on members’ qualifications and experience, while ignoring the importance of processes and variables emerging from a 360-degree evaluation. The purpose of this paper is to determine the effectiveness of audit committee self-evaluation in the South African public sector when the 360-degree approach is used. This paper draws its understanding of the 360-degree evaluation method’s effectiveness from the literature and qualitative methods reviewed. A semi-structured interview was conducted with individual directors of internal audit and members of their audit committees to obtain their expert opinions. Both convenience and snowball sampling methods were used to select the participants. Participants were drawn from the nine Provincial Treasuries and from their audit committees in the public sector. The paper finds that the 360-degree evaluation method is not being used by the audit committees of provincial entities as a self-assessment tool, and neither is its use elsewhere fully compliant with National Treasury’s requirements. The results further indicate that the governance structures, management and internal auditors of these entities are not using the 360-degree evaluation tool to its full potential when assessing the audit committee’s effectiveness. Therefore, this paper proposes that the National Treasury makes greater effort to promote the implementation of the 360-degree evaluation approach to audit committee performance, one that recognises the unique characteristics of public sector audit committees and their stakeholders. Keywords: 360-degree evaluations, Audit committees, Effectiveness, Public sector, Self-evaluation
Article published in: The 3rd Annual International Conference on Public Administration and Development Alternatives, 04 - 06 July 2018, Stellenbosch University, Saldahna Bay, South Africa
Keywords: 360-degree evaluations; Audit committees; Effectiveness; Public sector; Self-evaluation; Social service - Evaluation